Hypercoagulability in Vestibular Schwannoma Surgery. Issue 2 (February 2021) - Muelleman, Thomas J.; Alonso, Jose; Barnard, Zachary R.; Maxwell, Anne K.; Mahboubi, Hossein; Stefan, Michael; Lekovic, Gregory P.; Slattery, William H.; Brackmann, Derald E.
Abstract : Objective: Patients with vestibular schwannoma who harbor a genetic predisposition for venous thromboembolism require special consideration when determining optimal therapeutic management. The primary objective of the current study was to provide recommendations on treatment of hypercoagulable patients with vestibular schwannoma through a case series and review of the literature. Patients: Two patients who underwent resection of vestibular schwannomas. Intervention(s): Surgical resection and diagnostic testing. Main Outcome Measure(s): Postoperative venous thromboses. Results: One patient who underwent resection of vestibular schwannoma and suffered several postoperative thrombotic complications consistent with a clinical thrombophilia. One patient with known Factor V Leiden deficiency who underwent resection of vestibular schwannoma followed by postoperative chemoprophylaxis with a direct factor Xa inhibitor and experienced an uneventful postoperative course. Conclusions: In patients with a known propensity for venous thromboembolism, the skull base surgeon should consider nonsurgical management. If the patient undergoes surgical resection, we recommend careful effort to minimize trauma to the sigmoid sinus. In addition, the surgeon may consider retrosigmoid or middle fossa approaches. Best practice recommendations include the use of pneumatic compression devices, early ambulation, and consideration of postoperative prophylactic anticoagulation in patients with a known genetic predisposition.